Models for Evaluating the Effectiveness of Corporate Training Programs for Managers on the Principle of Cross-Functionality - M. I. Inozemtsev; M. K. Marushina; A. M. Mirzoyeva (Высшее образование в России)
The article focuses on the analysis of models for efficiency evaluation of corporate training programs for managers based on the principle of cross-functionality taking into account the type of educational organization. According to the authors, the expected results of corporate re-training of managers on the basis of cross-functionality, first of all, is the formation of diverse, additional competences. The emergence of new types of employees with diverse competencies who follow certain rules of relations between employees contributes to the consistent increment of innovative knowledge among employees, which fully corresponds to the changing needs of production and the digital economy. The work was carried out on the basis of study of Russian and foreign scientific publications, practical experience of authors and the survey of developers of corporate training programs and specialists on the basis of the principle of cross-functionality. The 7 most commonly used assessment models have been identified. The results are of interest to corporate training and continuing education professionals during the planning and development phase of educational programs.